Factores de riesgo cardiovascular y evolución de pacientes con COVID-19 atendidos en un Hospital Nacional de Referencia de Lima, P - Valenzuela-Rodríguez, Germán V. (2021)
Introduction: Coronavirus disease 2019 (COVID-19) fatal outcomes have been associated with multiple cardiovascular risk factors. In new epidemic areas, such as Latin America, there is a lack of studies about this. Objectives: To evaluate demographic data, signs and symptoms during emergency arrival, prevalence of cardiovascular risk factors, laboratory and ECG findings and their influence in mortality, in a retrospective cohort of patients in a national reference hospital of Lima, Peru. Methods: Review the clinical records of the patients attended at Hospital Rebagliati Hospital during March 6th and April 30th, 2020, using rRT-PCR was used for the detection of the RNA of SARS-CoV-2 following the protocol Charité, Berlin, Germany, from nasopharyngeal swabs at the National Institute of Health. Bivariate analysis and multivariate analysis using logistic regression was done. Values of p < 0.05 were considered significant for all analyses. Results: One hundred six hospitalized patients were evaluated. The mean age of patients was 61.58 years (SD 16.81). Cardiovascular risk factors among them were hypertension (46.2%), diabetes (28.3%), and obesity (28.3%), among others. Fifty-six patients died (52.8%). Mortality associated factors at the multivariate analysis were arterial hypertension (OR=1.343, 95% 1.089-1.667), myocardial injury (OR=1.303, 95% 1.031-1.642), and mechanical ventilation (OR 1.262, 95% 1.034-1.665), as associated factors. Conclusion: Cardiovascular risk factors and cardiovascular signs or symptoms are common during emergency arrival in patients with COVID-19. Arterial hypertension, myocardial injury and mechanical ventilation were associated with mortality in multivariate analysis, as observed in other regions of the world.